1977
DOI: 10.21273/jashs.102.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Tomato Fruit Size and Yield by Ozone1

Abstract: A multiple regression analysis of yields of ‘6718 VF’ tomato (Lycopersicon esculentum Mill.) from 11 field plots along an ambient ozone gradient in southern California indicated that ozone was responsible for a significant reduction in fruit size. Ozone dose accounted for 85% of the reduction in fruit size and was at least 3.3 times more important than any of the monitored meteorological variables in predicting the percentage of marketable fruit. High ambient ozone depressed production and caused a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tomato plants have exhibited significant reductions in yield in response to the air pol lutant ozone (10,14,15,16). Quality of the fruit harvested from plants exposed to ozone may also be altered.…”
Section: Quality Of Tomatoesmentioning
confidence: 99%
“…Tomato plants have exhibited significant reductions in yield in response to the air pol lutant ozone (10,14,15,16). Quality of the fruit harvested from plants exposed to ozone may also be altered.…”
Section: Quality Of Tomatoesmentioning
confidence: 99%
“…Several reports describe differences in severity of foliar symptoms among tomato germplasm (7,8,13,24). However, it has not been demonstrated that air pollutants reduce yield or quality of tomatoes (18,21,22,23). Thus a breeder must decide if he should make a concerted effort to select for air pollution tolerance or rely on chance selection for tolerance to ubiquitous pollutants.…”
Section: Air Pollutantsmentioning
confidence: 99%